Conditions of the Basra District in the reports of Administrative Inspector Amin Khalis (1951-1952) - Dawood Salman Al-Shalal, Assist. Prof. Dr. Faraqd (Basra studies journal, 2025)
The Basra Brigade enjoyed what other Iraqi brigades did not have in terms of a distinguished strategic location, which gave it a great economic and cultural importance, because it is considered the gateway to the Arabian Gulf from the north, and Iraq’s only maritime outlet for all countries of the world. In addition its possession of this status led to the emergence of many personalities, houses, and distinctive families, which had a great impact on the development of the economic, social and intellectual conditions of the Basra District, in addition to the thousands of farms and orchards and the presence of many factories and government laboratories. So the Ministry of Interior paid great attention to the Basra District through administrative inspection reports to diagnose weaknesses in government institutions and repair them as much as possible. They chose Amin Khalis to carry out this mission during the years (1951-1953).